Automated VMAT planning for short-course radiotherapy in locally advanced rectal cancer - Qiong Zhou; Liwen Qian; Chong Shen; Xinyan Bei; Gaojie Liu; Xiaonan Sun (PLoS ONE, 2025)
Purpose This study aims to develop a fully automated VMAT planning program for short-course radiotherapy (SCRT) in Locally Advanced Rectal Cancer (LARC) and assess its plan quality, feasibility, and efficiency. Materials and methods Thirty LARC patients who underwent short-course VMAT treatment were retrospectively selected from our institution for this study. An auto-planning program for neoadjuvant short-course radiotherapy (SCRT) in LARC was developed using the RayStation scripting platform integrated with the Python environment. The patients were re-planned using this auto-planning program. Subsequently, the differences between the automatic plans (APs) and existing manual plans (MPs) were compared in terms of plan quality, monitor units (MU), plan complexity, and other dosimetric parameters. Plan quality assurance (QA) was performed using the ArcCHECK dosimetric verification system. Results Compared to MPs, the APs achieved similar target coverage and conformity, while providing more rapid dose fall-off. Except for the V5Gy dose level, other dosimetric metrics (V25 Gy, V23 Gy, V15 Gy, Dmean, etc.) for the small bowel were significantly lower in the AP compared to the MP (p < 0.001). Additionally, the dosimetric parameters for the bladder, pelvic marrow, and femoral head were also lower in the AP, except for the V25Gy for the bladder. The MUs of the AP were approximately 4% lower than those of the MP. The AP showed high consistency in dosimetric parameters across five organs at risk (OARs). Conclusion We developed a fully automated, feasible SCRT VMAT planning program for LARC. This program significantly enhanced plan quality and efficiency while substantially reducing the dose to OARs.